2007
DOI: 10.1162/jocn.2007.19.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Amygdala and Ventromedial Prefrontal Cortex Activity are Associated with Evaluation Speed and Psychological Well-being

Abstract: Using functional magnetic resonance imaging, we examined whether individual differences in amygdala activation in response to negative relative to neutral information are related to differences in the speed with which such information is evaluated, the extent to which such differences are associated with medial prefrontal cortex function, and their relationship with measures of trait anxiety and psychological well-being (PWB). Results indicated that faster judgments of negative relative to neutral information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
110
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(118 citation statements)
references
References 54 publications
7
110
0
1
Order By: Relevance
“…Neurally, researchers used functional MRI to examine how people's amygdala activation differed in response to negative versus neutral stimuli. People with higher purpose displayed increased ventral anterior cingulated cortex activation and reduced amygdala activation (26). Another study used structural MRI and found that purpose was positively associated with right insular cortex gray matter and negatively associated with middle temporal gyrus gray matter (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurally, researchers used functional MRI to examine how people's amygdala activation differed in response to negative versus neutral stimuli. People with higher purpose displayed increased ventral anterior cingulated cortex activation and reduced amygdala activation (26). Another study used structural MRI and found that purpose was positively associated with right insular cortex gray matter and negatively associated with middle temporal gyrus gray matter (27).…”
Section: Discussionmentioning
confidence: 99%
“…Further work has linked purpose to better regulation of physiological systems (e.g., reduced inflammatory markers and cardiovascular risk factors) as well as brain-based mechanisms (e.g., insular cortex volume, reduced amygdala activation, sustained ventral striatum activation) (22)(23)(24)(25)(26)(27)(28)(29)(30). Additionally, a study that examined gene transcriptional profiles found that eudaimonic well-being (an overarching umbrella term that includes purpose) was associated with enhanced expression of antiviral response genes and reduced expression of proinflammatory genes (31).…”
mentioning
confidence: 99%
“…One possibility is that activation of the rACC in response to fearful faces exerts a regulatory influence over the amygdala (6)(7)(8)(9)(10)(11)(12)(13) and lower amygdala activation to fearful faces predicts a more beneficial outcome in terms of reported anxiety with venlafaxine. This hypothesis is consistent with anatomical data in nonhuman primates showing that the multiple regions of the ACC that send direct projections to the amygdala include a more dorsal portion of the rACC (4) similar to that identified here in humans, as well as a recent report suggesting that the outputs from the ACC to the amygdala greatly outnumber the amygdala's reciprocal inputs (35).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the ACC is part of a neural circuit that can provide regulatory control over the amygdala (5)(6)(7)(8)(9)(10)(11)(12). This control can occur spontaneously (6), can be directed (7)(8)(9)(10), or can occur in reaction to a change in environmental contingencies (e.g., extinction) (11,12). Of specific relevance to the present experiment are data showing that greater rostral ACC (rACC) reactivity in response to facial expressions of emotion is correlated with lesser amygdala reactivity (6,7).…”
mentioning
confidence: 99%
“…Indeed, overtly looking away from aversive stimuli facilitates emotion suppression (van Reekum et al, 2007) but also directing gaze towards aversive information (Bebko, Franconeri, Ochsner, & Chiao, 2011).…”
Section: Emotion Suppression and Emotional Attention 11mentioning
confidence: 99%